"Determinants of economic diversification in Malaysia" - Case study: Advantages to benefit for the Algerian national economy - - Fouzia Boutalbi; Fatima Belkhir (Journal of Excellence for Economics and Management Research, 2025)
This study analyzes Malaysia’s experience in economic diversification as a reference modelfor developing countries, with a particular emphasis on lessons applicable to Algeria. Throughstrategic planning, investment in human capital, and effective public-private partnerships, Malaysia successfully transitioned from a rentier economy to a diversified, innovation-drivenmodel. The study highlights the structural reforms and public policies that enabled this transformation and relates them to Algeria’s context, where reducing dependence on hydrocarbons and building a more diverse, resilient, and competitive economy remain key priorities. The study recommends institutional reforms, value-added industrial strategies, infrastructure development, and the strengthening of international partnerships as essential pillars for achieving economic diversification in Algeria.